Carbon Pool in Quercus lanuginose (D. Don) Forest of Askot Wildlife Sanctuary, Western Himalaya in Relation to Stand Attributes - Bargali, Kiran; Bisht, Soni; Bargali, S.S.; Rawat, P.S.; Rawat, Y. S. (Indian Forester, 2022)
Following the acceptance of the Kyoto Protocol, data on forest biomass must be collected in order to determine the potential ability of forest stands to sequester atmospheric carbon and aid in the reduction of rising carbon dioxide levels in the atmosphere. The aim of this study was to estimate the amount of carbon fixed by one of the overexploited oak species (Quercus lanuginosa) in Askot Wildlife Sanctuary Western Himalaya, India. Thirty quadrats of 10x10 m size were placed randomly at three altitudes between 1900 and 2100 m asl and data on biomass and soil characteristics were collected. In three forest sites CBH (circumference at breast height) of 236 individuals with a diameter of ≥31 cm was measured and standing biomass was estimated following growing stock volume equations. Across the sites, the mean aboveground and belowground carbon stock was 475.8±84.9 and 119.8±18.1 Mg C ha-1, respectively. The total tree carbon stock showed significant (P<0.01) positive correlation with soil carbon (R2= 0.71) and nitrogen (R2= 0.99). Basal area showed significant positive while diversity showed significant negative correlation with carbon stock. High carbon accumulation potential in old-growth individuals of Rianj oak suggests that they should be maintained in the study area to mitigate the effect of climate change.